Abundance and diversity of Bacillus thuringiensis in Bangladesh and their cry genes profile - Shishir, Asaduzzaman; Roy, Arpita; Islam, Namista; Rahman, Alamgir; Khan, Shakila N.; Hoq, Md. Mozammel (Frontiers in Environmental Science, 2014)
Bacillus thuringiensis (Bt) biopesticides, a recognized eco-friendly pest control agent, can be used to reduce many problems associated with indiscriminate use of chemical pesticides such as environmental pollutions, public health problems, emergence of resistance among pests in many developing countries etc. Bt strains were, therefore, isolated from different ecosystems of Bangladesh and characterized based on biochemical typing, 16S rRNA gene analysis, plasmid and cry genes profiles. Bt index was calculated 0.86 in this study and variations in abundance and distribution pattern of 16 different biotypes were demonstrated within 316 indigenous Bt strains which was compared to the other parts of the world. Bt indiana (17.8%), Bt kurstaki (16.7%) and Bt thuringiensis (12.7%) were found to be the most prevalent in Bangladesh among other biotypes. Hemolytic activity was variable among the biotypes and it was maximum for Bt biotype 10 (100%). Plasmids in the biotypes indiana, kurstaki, thuringiensis and israelensis were observed to occupy a wider range than other biotypes. The screening for insecticidal genes viz. cry1, cry2, cry3, cry4A, cry8, cry9, cry10 and cry11 in the native Bt strains revealed their presence in varied proportion rendering cry1, cry2 and cry3 the most abundant. The abundance of Bt strains, their diversities and the cry genes profile were thus analyzed in this study which will be the basis for further research development with Bt biopesticide in Bangladesh.